Are football players more prone to muscle injury after COVID-19 infection? The "Italian Injury Study" during the Serie A Championship - Corsini, A.; Bisciotti, A.; Canonico, R.; Causarano, A.; Del Vescovo, R.; Gatto, P.; Gola, P.; Iera, M.; Mazzoni, S.; Minafra, P.; Nanni, G.; Pasta, G.; et al. (International Journal of Environmental Research and Public Health, 2024)
Introduction: Football was the first sport to resume competitions after the coronavirus disease 2019 (COVID-19) lockdown and promptly the hypothesis was raised of a potential relationship between the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and musculoskeletal injuries in athletes. This study aimed to confirm the association between SARS-CoV-2 infection and muscle strain injury in a large population of elite football players and to investigate if the COVID-19 severity level could affect the risk of injury.